The Effect of Structured Music Activities on Executive Function in Kindergarten Children: A Quasi-Experimental Study - Ruani Oskar; Rahul Chan; Muhammad Sirozi (Journal of Social Work and Science Education, 2026)
This study aims to analyze the effect of structured music activities on the development of executive function in kindergarten-aged children at Bina Insan Islamic School Kindergarten. The study used a quasi experimental design with an experimental group and a control group. The subjects were kindergarten children in Group B. The experimental group participated in structured music activities that included singing, rhythm, and guided music games for eight weeks, while the control group participated in regular learning activities. Measurements of executive function included inhibitory control, working memory, and cognitive flexibility through standardized observations and teacher assessment sheets. Data were analyzed using comparative statistical tests. The results showed a significant increase in executive function in children in the experimental group compared to the control group, especially in aspects of self-control and the ability to follow rules. Structured music activities can be integrated as an effective learning strategy in early childhood education. This study highlights structured music as an Islamic school-based educational intervention. This research enriches early childhood education studies related to the development of executive function through a musical approach.